PANCASILA SEBAGAI GRUNDNORM MENURUT TEORI HUKUM MURNI HANS KELSEN DAN TEORI HUKUM RESPONSIF OLEH PHILIPPE NONET DAN PHILIP SELZNICK - Djauzie, Muhamad Zaky (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study discusses the role of the state foundation, responsive legal theory, and the philosophical values ​​of Pancasila in developing a relevant and quality legal system. Using a qualitative approach, this study synthesizes Hans Kelsen's "grundnorm" theory and Philippe Nonet's and Philip Selznick's responsive legal concepts. Kelsen emphasized the importance of a stable legal hierarchy for legal legitimacy, while responsive legal theory highlights the flexibility of law in dealing with social dynamics. The results of the study indicate that Pancasila functions as a "grundnorm" in the Indonesian legal system, providing a moral, cultural, and philosophical basis for creating justice and prosperity. The integration of Pancasila values ​​with a structural and responsive approach produces an inclusive, adaptive, and sustainable legal system. It can be concluded that the combination of the state foundation, responsive law, and philosophical values ​​allows for a legal system that is responsive to social change without losing its legitimacy and basic principles.